Clinical and Molecular Epidemiology of Stenotrophomonas maltophilia in Pediatric Patients From a Chinese Teaching Hospital - Duan, Zhongliang; Qin, Juanxiu; Li, Cui; Ying, Chunmei (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: To study the molecular epidemiological characteristics of Stenotrophomonas maltophilia (SMA) isolated from patients in a pediatric teaching hospital in Shanghai so as to provide data for the prevention and treatment of SMA. Methods: Non-repetitive SMA strains were isolated from patients from January 2013 to December 2014. The cloning characteristics were analyzed using multilocus sequence typing (MLST), and the drug resistance was determined using the Kirby-Bauer disk method. Virulence genes and biofilm genes were detected using polymerase chain reaction (PCR). The biofilm forming ability was analyzed using the semi-quantitative biofilm formation test. Results: A total of 104 strains were collected, primarily from the pediatric intensive care unit and thoracic surgery, and these strains were isolated from sputum sources (n = 82). A majority of the patients were male (67/104), and the age range was between 6 days and 12 years old. A total of 95 patients had 1–3 baseline diseases. All of the patients had prior use of 1–4 antimicrobial agents. A total of 59 STs were detected using the MLST analysis, of which 45 were new. The sequence types of the SMA were scattered, with no trend in the clonal spread. All of the strains were susceptible to levofloxacin, trimethoprim/sulfamethoxazole, and minocycline. The positive rates of the virulence genes stmPr1, stmPr2, smf-1, and smlt3773 locus were 98.1%, 86.5%, 100%, and 91.3%, respectively. All of the strains had biofilm formation, and most of the strains had strong biofilm formation abilities. The positive rates of the three biofilm genes rmlA, spgM, and rpfF were 83.7%, 100%, and 45.2%, respectively. However, the point mutations of rmlA and spgM with strong biofilm formation abilities were significantly different from those with weak biofilm formation abilities. Conclusion: Most infected patients had prior use of antibiotics and underlying diseases, and the positive rate of the virulence gene was high. The strains were susceptible to three kinds of antibiotics and had strong biofilm formation abilities. The mutations of rmlA and spgM may be related to the biofilm formation ability, and no obvious clonal transmissions were found in the same clinical department.